Mitochondrial topoisomerase 1 inhibition induces topological DNA damage and T cell dysfunction in patients with chronic viral infection - Dang, Xindi; Cao, Dechao; Zhao, Juan; Schank, Madison; Khanal, Sushant; Nguyen, Lam Ngoc Thao; Wu, Xiao Y.; Zhang, Yi; Zhang, Jinyu; Jiang, Yong; Ning, Shunbin; Wang, Ling; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
T cells play a pivotal role in controlling viral infections; however, the mechanisms that dampen their responses during chronic viral infections remain incompletely understood. In this study, we investigated the role and mechanisms of mitochondrial topoisomerase 1 (Top1mt) inhibition in mitochondrial dysfunction and T cell dysregulation using CD4 T cells from patients with HCV and HIV infection, as well as healthy CD4 T cells treated with Top1 inhibitor - camptothecin (CPT). We demonstrated that Top1mt protein expression and enzymatic activity are significantly inhibited, along with Top1 cleavage complex (Top1cc) formation, in mitochondria of CD4 T cells from HCV and HIV patients. Notably, treatment of healthy CD4 T cells with CPT caused similar topological changes, including accumulation of Top1cc in mitochondria, inhibition of Top1mt, increase in PARP1 cleavage, and decrease in mtDNA copy numbers. These molecular changes resulted in mitochondrial dysfunction, T cell dysregulation, and programmed cell death through multiple signaling pathways, recapitulating the phenotype we observed in CD4 T cells from HCV and HIV patients. Moreover, treatment of CD4 T cells from HCV or HIV patients with CPT further increased cellular and mitochondrial reactive oxygen species (ROS) production and cell apoptosis, demonstrating an important role for Top1 in preventing mtDNA damage and cell death. These findings provide novel insights into the molecular mechanisms underlying immunomodulation during viral infection and indicate that Top1 inhibition due to HCV or HIV infection can induce mtDNA damage and T cell dysfunction. Thus, reconstituting Top1 protein may restore the mtDNA topology and offer a new strategy for maintaining T cell function during viral infection.